2015
DOI: 10.17584/rcch.2015v9i1.3744
|View full text |Cite
|
Sign up to set email alerts
|

Resultados preliminares del efecto del riego deficitario durante el periodo de crecimiento rápido del fruto de pera (var. Triunfo de Viena) en la producción y calidad del fruto

Abstract: Plantulas de tomate.Foto: Álvarez-Herrera.Resultados preliminares del efecto del riego deficitario durante el periodo de crecimiento rápido del fruto de pera (var. Triunfo de Viena) en la producción y calidad del fruto Preliminary results of the effect of deficit irrigation during the rapid growth of the pear fruit on production and quality of Triunfo de Viena variety RESUMENEl objetivo de este trabajo se centró en estudiar la respuesta del peral (var. Triunfo de Viena) al riego deficitario durante la fase de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 6 publications
(7 reference statements)
1
1
0
1
Order By: Relevance
“…As the treatments progressed, the equatorial diameter in the control treatment was greater than in the treatments with RDI for the two years; however, after the resumption of irrigation, the fruits from plants with an application of 60% of the ETc had a compensatory growth and reached the equatorial diameter of the fruits of the control treatment, similar to what was found by Vélez et al [35]. The equatorial diameters measured in 2014 at 154 DAF (7.69, 8.32 and 7.69 cm) were greater than those found in two other studies on pears, with 7.07, 6.93 and 6.83 cm [29] and 6.65, 6.16 and 6.17 cm [31]. Meanwhile, the values found in the present work in 2015 at 186 DAF (7.53, 7.34 and 7.50 cm) were lower when the plants were irrigated with 100, 48 and 27% of the ETc, respectively, which can be attributed to the higher median maximum temperatures in 2014 (21 • C) compared to those of 2015 ( 16• C), and to the higher rainfall (233.44 mm in 2015, 465.4 mm in 2014).…”
Section: Production Parameterssupporting
confidence: 86%
See 1 more Smart Citation
“…As the treatments progressed, the equatorial diameter in the control treatment was greater than in the treatments with RDI for the two years; however, after the resumption of irrigation, the fruits from plants with an application of 60% of the ETc had a compensatory growth and reached the equatorial diameter of the fruits of the control treatment, similar to what was found by Vélez et al [35]. The equatorial diameters measured in 2014 at 154 DAF (7.69, 8.32 and 7.69 cm) were greater than those found in two other studies on pears, with 7.07, 6.93 and 6.83 cm [29] and 6.65, 6.16 and 6.17 cm [31]. Meanwhile, the values found in the present work in 2015 at 186 DAF (7.53, 7.34 and 7.50 cm) were lower when the plants were irrigated with 100, 48 and 27% of the ETc, respectively, which can be attributed to the higher median maximum temperatures in 2014 (21 • C) compared to those of 2015 ( 16• C), and to the higher rainfall (233.44 mm in 2015, 465.4 mm in 2014).…”
Section: Production Parameterssupporting
confidence: 86%
“…It was observed that, at the beginning of the water restriction, the fruit growth decreased slightly; however, when irrigation was restored to normal levels, or when rain fell, the growth recovered and the fruits reached the development of those of the control treatment, having accumulated dry weight in a similar way during the periods of water stress. This dry weight gain seems to be available to facilitate the compensatory growth of the fruit after the resumption of irrigation [28][29][30][31][32]. Table 1 shows that, in 2014, the application of 60% of ETc induced the highest percentage of dry weight in fruits, although without statistically significant differences.…”
Section: Production Parametersmentioning
confidence: 97%
“…Esto demuestra el mayor poder vertedero de la variedad Chonto grueso en términos de materia seca (41). …”
Section: Tasa Absoluta De Crecimientounclassified